Legal Implications of Electronic Contracts in Civil Law: A Case Study in the Digital Era - Simamora, Pinta N. S.; Ginting, Grenaldo; Rantung, Cindy Mariam Magdalena; Kaunang, Pingkan Dewi; Dewi, Putri Maha (Inovasi Pratama Internasional. Ltd, 2025)
This study explores the legal implications of electronic contracts (e-contracts) within the framework of Indonesian civil law, emphasizing the challenges and opportunities presented by digital transactions in the contemporary marketplace. Utilizing a qualitative research methodology, data were collected through literature reviews, document analysis, and semi-structured interviews with legal practitioners, academics, and e-commerce representatives. The findings reveal three key themes: Legal Validity, highlighting issues related to authentication and evidence admissibility; Legal Clarity, underscoring the need for specific regulations governing e-contracts and emerging technologies like smart contracts; and Consumer Protection, addressing jurisdictional complexities and the necessity for enhanced consumer awareness. The study concludes that while Indonesia recognizes e-contracts as legally binding, significant gaps remain in the regulatory framework that must be addressed to foster trust and innovation in the digital economy. Recommendations include developing clearer regulations, improving authentication processes, and strengthening consumer protection laws. This research contributes to the ongoing discourse on electronic contracting in Indonesia, providing insights that are essential for stakeholders navigating the evolving landscape of digital transactions.